Cognitive linguistics and sociocultural theory : applications for second and foreign language teaching - Masuda, Kyoko; Arnett, Carlee; Labarca, Angela (Studies in second and foreign language education ;, 2015)
By integrating cognitive linguistics and sociocultural theories, this groundbreaking book presents empirical studies on selected grammatical and semantic aspects that are challenging for second/foreign language learners. Through in-depth studies exploring eight different languages, this book offers insights generated through the synergy between cognitive linguistics and sociocultural theories that can be readily incorporated into teaching.